PGPR BioBoost : Powered by Sarawak's Sago Rhizobacteria - Samuel, Lihan; Nur Azzah, Osman; Flonia, Benet; Nisa Syahirah, Maulad Abdul Gani; Awang Ahmad Sallehin, Awang Husaini; Kasing, Apun; Hairul, Azman (2025)
The innovation of PGPR BioBoost centres on three elite PGPR strains—Bacillus cereus M063BA, Pseudomonas extremasurialis STA, and Serratia marcescens SUN—directly isolated from Sarawak’s acidic peat soils beneath sago palms. These bacteria are the engine of Sarawak’s bio-solution, delivering: 1. STA: The Nutrient Powerhouse • Unlocks trapped phosphorus: Solubilises 23.08 mg/L (highest recorded) • Boosts root growth: Produces 26.07 μg/mL IAA (natural growth hormone) • Fights iron starvation: Secretes iron-binding siderophores 2. M063BA & SUN: The Support System • Fix nitrogen + produce ammonia → replace synthetic fertilisers • Thrive in acidic peat (pH 4.5-5.5) → built for Sarawak’s harsh soils No chemicals. No genetic modification. Just nature’s finest microbiomes, harnessed for sustainable farming.